Strengthening Risk Management in Digital Financial Institutions (A Case Study of PT GVD) - Herawati, Ratih Dewi; Khudri, Tubagus M. Yusuf (E-Jurnal Akuntansi, 2025)
This study evaluates the risk management implementation at PT GVD, a digital financial company, using the COSO ERM framework and the Three Lines Model. A case study method was employed, utilizing data from questionnaires completed by 18 respondents and company documents, which were analyzed quantitatively using descriptive statistics. The evaluation results indicate that PT GVD’s risk management implementation is adequate but has several shortcomings, including a lack of process standardization and consistency, the need for improved human resource competency development, uneven understanding of risk appetite, absence of a comprehensive risk portfolio view, and limited use of quantitative data in risk evaluation. Therefore, this study recommends enhancing PT GVD’s risk management through strengthened communication, process standardization, HR training, and advanced analytics to support risk-based decision-making. The study also provides important contributions to the development of risk management evaluation based on COSO ERM and the Three Lines Model in the digital payment industry, particularly in developing countries. Keywords: COSO ERM; Digital payment; Risk Management; Three Lines Model